Water quality assessment of Putrajaya Lake for alternative source of water supply - Nur Aqilah, Mohd Sabandi (2016)
This study focused on determining water quality of Putrajaya Lake. Water Quality is an important guideline to describe the physical, chemical, and biological properties of water that classified them into each class with different suitable purposes. A study was conducted on physical, chemical, and biological parameter of Putrajaya Lake in 2015 water bodies at five stations with three times sampling in the month of September,October, and November. Physical parameters were temperature and suspended solids. Whereas, chemical parameters were pH, dissolved oxygen (DO), biochemical oxygen demand (BOD), chemical oxygen demand (COD), ammoniacal nitrogen, and selected heavy metals. Biological parameter were Total Coliform and E. Coli. The water was classified based on Water Quality Index (WQI) and National Water Quality Standard for Malaysia (NWQS). According to WQI, the classifications of water quality were based on each station. The most stations in Putrajaya Lake were classified into Class I and II. Station 3 possessed the highest quality surface water sources with WQI value 95 and belongs to Class 1. Station 4 followed by 92, continues with Station 2, Station 5, and Station 1 with value 91,89, and 87 respectively and all of them belong to Class II. Based on NWQS, Most of parameters are belong to Class I. However, BOD, DO, Total Coliform, and lead presence are belongs to Class II. Station 4 chosen as most suitable sources for alternative water supply. The large area covered is the characteristic include in choosing Station 4 as the most suitable alternative water supply. However, in order to provide safe water supply, the raw water sources need to undergo conventional water treatment. According to the Raw Drinking Water Quality Standard the water in Lake Putrajaya did not pass the standards for COD and lead. The main source of lead in the Putrajaya Lake is due to the boating activities that became attraction of Putrajaya. Therefore, it is important to apply new technologies and ideas to control lead contamination. Overall, water quality determination is important to identify different suitable purpose of water body. It is important to conserve and preserve the source of surface water for water supply purpose to avoid water shortage in future.